Nas tramas da revitalização : conflitos e movimentos na zona portuária do Rio de Janeiro - Costa, Flávia Carolina Da (2016)
This thesis focuses on the observation and analysis of the connections among memory, conflict and politics in social network associations, neighborhoods and local sociabilities in the context of the urban “revitalization" in the port area of Rio de Janeiro. Presuming that a story is an individual expression limited by a "general discourse" that classifies feelings, understandings and significations of experience from a dominant culturally provided structure, this thesis is guided by the understandings of a symbolic universe based on memories that combine past and present with official and non-official perceptions of the city, told in multiple ways by the interlocutors of this research. Throughout the study the term "revitalization" is analyzed according to circumstances in which dweller and association categories were observed in the course of fieldwork as a constant "movement" of different artistic, political and cultural investments in the context of social transformations. The nonfixity of the resident category is due to the notion of "testimonial memories" and ethnographically understood as the operator of a system that activates relations and "ways of inhabiting" in the port area, primarily from a political point of view.